Circumnutational movement in rice coleoptiles involves the gravitropic response: analysis of an agravitropic mutant and space‐grown seedlings. Issue 3 (2nd October 2018) - Kobayashi, Akie; Kim, Hye‐Jeong; Tomita, Yuta; Miyazawa, Yutaka; Fujii, Nobuharu; Yano, Sachiko; Yamazaki, Chiaki; Kamada, Motoshi; Kasahara, Haruo; Miyabayashi, Sachiko; Shimazu, Toru; Fusejima, Yasuo; et al.
Abstract : Plants exhibit helical growth movements known as circumnutation in growing organs. Some studies indicate that circumnutation involves the gravitropic response, but this notion is a matter of debate. Here, using the agravitropic rice mutant lazy1 and space‐grown rice seedlings, we found that circumnutation was reduced or lost during agravitropic growth in coleoptiles. Coleoptiles of wild‐type rice exhibited circumnutation in the dark, with vigorous oscillatory movements during their growth. The gravitropic responses in lazy1 coleoptiles differed depending on the growth stage, with gravitropic responses detected during early growth and agravitropism during later growth. The nutation‐like movements observed in lazy1 coleoptiles at the early stage of growth were no longer detected with the disappearance of the gravitropic response. To verify the relationship between circumnutation and gravitropic responses in rice coleoptiles, we conducted spaceflight experiments in plants under microgravity conditions on the International Space Station. Wild‐type rice seeds were germinated, and the resulting seedlings were grown under microgravity or a centrifuge‐generated 1 g environment in space. We began filming the seedlings 2 days after seed imbibition and obtained images of seedling growth every 15 min. The seed germination rate in space was 92–100% under both microgravity and 1 g conditions. LED‐synchronized flashlight photography induced an attenuation of coleoptile growth and circumnutational movement due to cumulative light exposure. Nevertheless, wild‐type rice coleoptiles still showed circumnutational oscillations under 1 g but not microgravity conditions. These results support the idea that the gravitropic response is involved in plant circumnutation.